2013 Physics Education Research Conference Proceedings 2014
DOI: 10.1119/perc.2013.pr.064
|View full text |Cite
|
Sign up to set email alerts
|

Can Visual Cues and Correctness Feedback Influence Students' Reasoning?

Abstract: Abstract. Research has demonstrated that attentional cues overlaid on diagrams and animations can help students attend to the relevant areas and facilitate problem solving. In this study we investigate the influence of visual cues and correctness feedback on students' reasoning as they solve conceptual physics problems containing a diagram. The participants (N=90) were enrolled in an algebra-based physics course and were individually interviewed. During each interview students solved four problem sets each con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…This study was part of a larger study in which we investigated the effect on problem correctness due to both feedback and visual cues ( Rouinfar et al, 2014 ). In this paper we focus on the analysis of the eye movement data, though we use accuracy data to show evidence of learning to make arguments linking the eye movements to learning.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a larger study in which we investigated the effect on problem correctness due to both feedback and visual cues ( Rouinfar et al, 2014 ). In this paper we focus on the analysis of the eye movement data, though we use accuracy data to show evidence of learning to make arguments linking the eye movements to learning.…”
Section: Methodsmentioning
confidence: 99%
“…Midwestern university received extra credit equal to 1% of their course grade as incentive for participation in our study. The materials were conceptual physics problems with diagrams similar to those from a previous study [3]. Students were randomly assigned to three conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We did not have a fourth (control) condition receiving neither solutions nor cues because previous work has already shown that the control condition is outperformed by the cued condition [3]. Students were interviewed individually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students received extra credit equal to 5% of the course grade for participating in a 60-minute long interview containing four problem sets. The problem sets were based on our previous work [5], and named -Ball, Graph, Skier, and Roller Coaster. Each set consisted of one initial problem, six training problems, a near transfer problem, and a far transfer problem presented on a computer screen.…”
Section: Methodsmentioning
confidence: 99%